Reproductive phenotype of two lines of Japanese quail (Coturnix coturnix japonica) under two different room temperatures - A.G Nataamijaya (Indonesian Center for Animal Research and Development (ICARD), 2003)
Line as well as ambient temperature, substantially affected the reproductive performance of birds, hence in this study lines C (control) and P (meat type) were assigned into two room temperatures i.e. 18 and 35°C, represented higher and lower land areas of Indonesian archipelago. This study was conducted to find out the effect of line, ambient temperature and it’s interaction on the reproductive phenotype of Japanese quail. A Completely Randomed Design with 23 factorial arrangement was applied using 8 males and 24 females of each room temperature, every bird was kept in individual cage. Each male was mated to one female for 5 minutes per day for 3 consecutive days, 15 days later the same male was mated to the second female using the same manner. The third female was mated to this male using the same previous way. Parameters measured were copulation number, egg mass, testes weight, fertility and duration of fertility. Results showed that copulation number of line P (1.10 ± 0.29) were lower than (P<0.05) that of line C (1,84 ± 0,33). Within 14 day period line P produced higher egg mass compared with line C (66.91 g vs 55.88 g). Line P testis weight (6.82 ± 0.36 g) were significantly (P<0.01) higher than that of line C (3.18 ± 0.34 g), while room temperature slightly affected the testis weight. Fertility rate of line P (29.07 ± 14.12%) was much lower (P<0.01) than that of line C (46.90 ± 15.44 %). Duration of fertility of line P (1.10 ± 0.35 days) was also lower (P<0.01) than that of line C (3.48 ± 1.28 days). Copulation number and egg mass were not influenced by high room temperature while rate and duration of fertility were substansially affected. It was concluded that some reproductive parameters of male and female of Japanese quail were affected by body weight and room temperature in different way. Key words: Line, quail, room temperature, reproductive